Investigation of the interrelated effects of temperature and frequency on fretting wear - Jin, Xiaozhe (2017)
This thesis concerns both experimental and modelling investigations of the interrelated effects of temperature and frequency on fretting wear. Experiments were conducted using a cylinder-on-flat contact configuration with 304 stainless steel under various environmental temperatures and fretting frequencies. Analytical and finite element (FE) models have been developed to predict the thermal field near the fretting contact, the friction behaviour, the plastic deformation and the wear scars.